Observaciones lingüísticas de Kavafis a la Gramática de Huber Pernot - Clair, Christos (Byzantion Nea Hellás, 2015)
The author examines a Kavafis' commentary on Pernot's THE GRAMMAR OF THE MODERN GREEK, which stayed as a manuscript until 1963. The author highlights the poet's objectivity in his approach to the Greek language's phenomena. This objective and respectful criterion towards the use and diversity on the part of Kavafis is remarkable - - considering thetime in which the commentary was written and the linguistic problem inGreece.At that time, modem linguistics was hardly doing its firsts steps andspreading its postulates. On the other hand, the strong "archaizing" greektradition had produced deep prejudices.Kavafis not only admitted the more frequent and common use, butalso duality and plurality of uses. It is also remarkable that the poet admittedthe aesthetic criterion before the variety of forms in use. It's worth to say thatthe aesthetic criterion is nowadays taken into account by socio-linguisticresearchs.Kavafis did not totally condemn the use of foreign words. On the contrary, he admitted them when there is not a Greek word for a concept or object, or when there is not possibility of creating a new word. Finally, the author values Kavafis' vast knowlwdge about theNeogreek linguistic bibliography.